MALDI imaging mass spectrometry: Spatial molecular analysis to enable a new age of discovery - Gessel, Megan M.; Norris, Jeremy L.; Caprioli, Richard M. (Journal of proteomics, 2014)
Matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI IMS) combines the sensitivity and selectivity of mass spectrometry with spatial analysis to provide a new dimension for histological analyses to provide unbiased visualization of the arrangement of biomolecules in tissue. As such, MALDI IMS has the capability to become a powerful new molecular technology for the biological and clinical sciences. In this review, we briefly describe several applications of MALDI IMS covering a range of molecular weights, from drugs to proteins. Current limitations and challenges are discussed along with recent developments to address these issues. This article is part of a Special Issue entitled: 20years of Proteomics in memory of Vitaliano Pallini. Guest Editors: Luca Bini, Juan J. Calvete, Natacha Turck, Denis Hochstrasser and Jean-Charles Sanchez. [Display omitted] •MALDI IMS has the capability to become a powerful new molecular technology for the bioligcal and clinical sciences.•Applications of MALDI IMS are described, covering a range of molecular weights, from drugs to proteins.•Current limitations and challenges are discussed, as well as recent developments that address these issues.